Upregulation of ARHGAP18 by miR-613 Inhibits Cigarette Smoke Extract-Induced Apoptosis and Epithelial-Mesenchymal Transition in Bronchial Epithelial Cells - Fu H; Liu K; Zheng Y; Zhao J; Xie T; Ding Y (International Journal of COPD)
Haifan Fu,1,2,* Kai Liu,3,* Yamei Zheng,3 Jie Zhao,3 Tian Xie,3 Yipeng Ding2,3 1Yangjiang Health Center of Qionghai County, Qionghai, Hainan Province, People’s Republic of China; 2Department of General Practice, Hainan Affiliated Hospital of Hainan Medical University, Hainan General Hospital, Haikou, People’s Republic of China; 3Department of Pulmonary and Critical Care Medicine, Hainan General Hospital, Hainan Affiliated Hospital of Hainan Medical University, Haikou, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yipeng Ding, Hainan General Hospital, No. 19, Xinhua Road, Xiuying District, Haikou, 570311, Hainan, People’s Republic of China, Tel +86 18976335858, Email ypding1961@163.comObjective: Chronic Obstructive Pulmonary Disease (COPD) is a major chronic respiratory disease affecting human health worldwide. However, there is still a lack of effective drugs for treating COPD. This study is intended to explore the function and molecular mechanism of ARHGAP18 and miR-613 in COPD pathogenesis.Methods: We initially identified the marker gene closely related to epithelial dysfunction in COPD by integrating bioinformatic analyses. ARHGAP18 expression in CSE-induced bronchial epithelial cells (BEAS-2B) was detected by qRT-PCR. Besides, ARHGAP18 levels were modulated by lentivirus-mediated overexpression. Thereafter, cell variability, apoptosis, and migration were detected by CCK8, flow cytometry, and wound healing assay. IL-1β and TNF-α levels were examined by qRT-PCR. Epithelial-mesenchymal transition (EMT)-associated proteins were determined by Western blotting. The function of miR-613 in COPD was further detected. Functional rescue experiments were performed to determine the mechanism of ARHGAP18 in COPD.Results: Our study identified ARHGAP18 as the key gene associated with epithelial dysfunction in COPD. ARHGAP18 was downregulated in CSE-induced BEAS-2B cells. Overexpression of ARHGAP18 inhibited cell apoptosis of BEAS-2B cells and enhanced their proliferation and migration. Besides, ARHGAP18 overexpression reduced IL-1 β and TNF-α levels, enhanced E-cadherin expression, and suppressed Vimentin and N-cadherin expression. In contrast, miR-613 mimics exerted opposite effects. Furthermore, downregulation of ARHGAP1, mediated by miR-613 inhibitor promoted cell apoptosis and EMT of CSE-induced BEAS-2B cells, suggesting a regulatory role of miR-613 in COPD pathogenesis.Conclusion: These findings highlight miR-613/ARHGAP18 axis as a critical regulator of epithelial dysfunction in COPD, offering a potential therapeutic target to counteract apoptosis, inflammation, and airway remodeling.Keywords: chronic obstructive pulmonary disease, ARHGAP18, apoptosis, epithelial-mesenchymal transition, miR-613